A comparison study on aqueous humor transforming growth factor-beta (TGF-β) and vascular endothelial growth factor (VEGF) level in primary glaucoma patients and controls - Samsudin, Norhayaty (2017)
INTRODUCTION Glaucoma can be classified into two main groups according to the angle structure; closed angle glaucoma and open angle glaucoma. Open and closed angle glaucoma can further be classified into primary or secondary glaucoma. Primary open angle glaucoma (POAG) is the most common type of glaucoma. Primary angle closure glaucoma (PACG) has been noted to have a relatively high prevalence in Southeast Asia, and to be a leading cause of blindness in this region. Transforming growth factor (TGF- β) regulates the proliferation and differentiation of cells, embryonic development, wound healing, and angiogenesis. Vascular growth endothelial factor (VEGF) is a signaling peptide produced by cells to stimulate both vasculogenesis and angiogenesis. In the process of wound healing, there is a complex interplay of mediators comprised of growth factors, cytokines and chemokines. Understanding the role of growth factors such as TGF-β and VEGF in the ocular wound healing cascade may increase the success rate of glaucoma filtering surgery and knowledge on pathogenesis of primary glaucoma.OBJECTIVE To compare the transforming growth factor- beta (TGF-β) and vascular growth endothelial factor (VEGF) level in aqueous humor of primary glaucoma patients and controls.METHODOLOGY This prospective cross-sectional study was conducted between November 2013 and February 2017 at Hospital Universiti Sains Malaysia. In total, 63 eyes of 63 patients undergoing cataract surgery or primary augmented trabeculectomy surgery were included in this study. Recruited subjects were classified into primary glaucoma (POAG and PACG) group and control group. Aqueous humor samples were prospectively collected at the beginning of surgery from 32 eyes with primary glaucoma (16 POAG and 16 PACG) and from 31 control eyes that underwent cataract operation and primary augmented trabeculectomy. The concentration of TGF-β and VEGF levels was measured by using enzyme-linked immunosorbent assay test (ELISA). RESULTS The median concentration (interquertile range (IQR) of TGF-β in the aqueous humor of eyes with POAG was 2432.50 ± 3233.57 pg/ml, 1787.40 ± 1650.37 pg/ml in PACG and 1571.40 ± 409.20 pg/ml in controls. Median levels of TGF-β were observed to be significantly higher in the POAG group and PACG group compared to controls (p = 0.004 and p = 0.015). However there was no significant difference between POAG and PACG patients (p = 0.300). There was also no significant differences in median levels of VEGF between patients with primary glaucoma compared to controls (p =0.085), or between POAG and PACG patients (p= 0.043). The median concentration of VEGF in the aqueous humor of eyes with POAGwas 518.58 ± 542.61 pg/ml, 307.69 ± 194.39 pg/ml in PACG and 330.20 ± 202.40 pg/ml in controls. CONCLUSION The aqueous humor TGF-β level was significantly higher in eyes with primary glaucoma compared to control. TGF-β in the aqueous humor may play a role in the pathogenesis of POAG and PACG. The aqueous humor VEGF level did not differ significantly between eyes with primary glaucoma compared to controls, and between eyes with POAG and PACG.